PENGARUH GOOD CORPORATE GOVERNANCE DAN INTELLECTUAL CAPITAL DISCLOSURE TERHADAP COST OF EQUITY CAPITAL - Putri Dwi Wahyuni; Wiwik Utami (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
This study aimed to examine the effect good corporate governance and intellectual capital disclosure on cost of equity capital. This research was conducted on issues of banking sector in the Indonesia Stock Exchange during the period 2012-2014. The sample of this research totally are 90 data from the manufacturing sector in the Indonesia Stock Exchange with a purposive sampling method. The analytical method used is multiple regression analysis. Statistical t-test was performed before analysis of multiple regression equation, in the first phase of testing performed classical assumption of normality, multicollinearity, heteroscedasticity, and autocorrelation. The next step is to test the hypothesis that is done using the t test to determine the effect of each independent variable. Based on the analysis, it is known that institutional ownership, managerial ownership, the proportion of independent board and the proportion of independent audit committees do not affect the cost of equity capital. While intellectual capital disclosure positive effect on the cost of equity capital. The coefficient of determination that saw the influence of the independent variables used in the study model of the dependent variable was 9.4%, while the rest (90.6%) is explained by other variables.